freshwater mollusks of medical importance in Kalasin Province, northeast Thailand - Pusadee Sri-aroon (2018)
A snail survey was performed in six districts around irrigation areas of Lampao Dam, in Kalasin Province. The survey caught a total of 5,479 live snails and classed them into five families, 12 genera and 15 species, of which 7 species are suspected of transmitting human parasitic diseases. The seven species were Pila polita, Pomacea canaliculate, Filopaludina (S.) m. martensi, Bithynia (Digoniostoma) siamensis goniomphalos, Melanoides tuberculata, Radix rubiginosa, and Indoplanorbis exustus. Of these, B. (D.) s. goniomphalos and I. exustus were found to harbor emergent cercariae. Only B. (D.) s. goniomphalos hosted several types of cercariae - Opisthorchis viverrini, unidentified species of intestinal flukes, echinostomes, xyphidio and furcocercous cercariae. Indoplanorbis exustus shed only echinostome cercariae. B. (D.) s. goniomphalos showed a rather high natural infection rate with O. viverrini, 1.3% in Yang Talat district, and 0.61% in Kamalasai district, in Kalasin Province.